PKM Industri Rumah Tangga Jajanan Khas Bali Di Desa Tegal Jadi, Kecamatan Marga, Kabupaten Tabanan, Provinsi Bali - Iswara, Ida Bagus Ary Indra; Wijaya, I Nyoman Saputra Wahyu; Willdahlia, Ni Putu Ayu Gede; Meinarni, Ni Putu Suci (Paradharma: Jurnal Aplikasi IPTEK, 2019)
ABSTRAK Usaha jajanan Bali traditional Dana Asih dan Riko Kaliadrem adalah industri rumah tangga (IRT) yang berlokasi di Br. Pengembungan, Desa Tegal Jadi, Kecamatan Marga, Kabupaten Tabanan. Kedua industri tersebut menyediakan berbagai jajanan khas Bali yang digunakan untuk upacara dan dikonsumsi. Jajanan khas Bali yang diproduksi adalah jaja uli, jaja begina dan jaja kaliadrem. Kegiatan bisnis yang dijalani kedua IRT ini diantaranya menerima pesanan jajanan khas Bali, memproduksi secara konvensional dari pemilihan bahan, kuantitas bahan yang digunakan, pengolahan bahan, pengemasan jajanan serta memasarkan hasil produksi. Produk yang dihasilkan oleh mitra adalah jajanan kering khas Bali. Produk tersebut dikemas kedalam plastik flip tanpa memberikan desain kemasan yang dapat menjadi identitas industri. Mitra mengakui produk yang mereka dijual di pasaran tidak dikenali oleh konsumen karena banyak produk yang sama. Hal tersebut mempengaruhi promosi yang diinginkan oleh mitra. Jajanan khas Bali yang dibuat tidak menggunakan bahan pengawet, sehingga diperlukan kemasan yang kedap udara agar produk dapat bertahan lebih lama. Permasalahan yang dialami mitra adalah pemasaran produk atau promosi serta pencatatan penjualan. Solusi yang diberikan adalah dengan merancang kemasan produk yang menarik dan kedap udara, memberikan pelatihan membuat jajanan khas Bali dengan resep baru yang lebih tahan lama, menyediakan sebuah website e-commerce serta mitra diberikan pelatihan menggunakan media sosial. Produk dapat dikenal pada khalayak umum dengan identitas pada kemasan serta masa kadaluarsa produk lebih lama. Varian rasa dari produk bertambah dengan harapan lebih diminati masyarakat. Kemampuan memanfaatkan teknologi juga meningkat yang dapat berpengaruh kepada peningkatan produktivitas.Kata kunci : jajanan, kemasan, promosi, e-commerceABSTRACT Traditional Balinese snacks are home industries businesses located in Br. Pengembungan, Tegal Jadi Village, Marga District, Tabanan Regency. Both industries has some kind of Balinese snacks that are used for ceremonies and also to consume. They are Jaja Uli, Jaja Begina and Jaja Kaliadrem. The business activities undertaken by these two home industries start from receiving orders for the snacks, producing conventionally, from selecting the ingredients, measuring the quantity of materials used, processing of materials, wrapping the snacks and selling of these products. These products can be classified into bali dry snacks. It is wrapped into a flip plastic that can be bought on the market without using special design for the packaging, which is it can be an industrial identity. Partners acknowledge that the products they sell on the market cannot be recognized by consumers because many other industry players sell the similar products. This will probably affects the promotion desired by partners. In addition, typical Balinese snacks that are made do not use preservatives, so airtight packaging is needed so that the product can last longer. The main problemsÂ experienced by partners and closely related to the packaging are product selling or promotion. The selling process carried out by partners (some sellers) is done conventionally. Partners keep their products limited in traditional markets. The impact that occurs in this marketing way is the demand for products does not increase. The next problem is recording sales. So far, business partners do not record sales in any form so that it cannot be clearly seen how many products have been sold and in what time period and cannot calculate the total profits that have been obtained. The solution offered is to design attractive and airtight product packaging, make recipes and provide training for recipes, provide an e-commerce website that can help the promotion process and record sales. Some courses will also be provide to partners for example the course about using social media. As the aim, the products will be famous into public. And the packaging design hopefully will give an identity that is including the product expiry date as a trustworthy product. The flavor variant of the product increases with the hope that the community is more interested. The ability to use technology also increases which can affect productivity.Key words : snacks, packaging, promotion, e-commerce